Efek Budaya Organisasi, Kompetensi terhadap Prestasi Kerja Personil Polisi bagian Ditshabara - Riza Efendi (STIA Indragiri, 2017)
ABSTRACTThe purpose of this study is to analyze the effect of the organizational culture, competency, and compensation on the work performance of police personnel at the regional police directorate Sabhara Riau islands. The scope of the variables in this study include organization culture, competency, dan compensation on the work performence of personnel.This study uses quantitative data from primal sources those that gathered through a questionnaires. Subjects of the research are all of police personnel at the regional police directorate Sabhara Riau islands. Data processing techniques used were the population method in which allof police personnel at the regional police directorate Sabhara Riau islands as a sampled in this study. Data analysis method used is testing instruments made by testing the validity and reliability. While the technique of data analysis used is descriptive analysis method, multiple linear regression analysis, and hypothesis testing. The results showed that simultaneous, system and procedure of the procurement and motivation have a significant effect on employee performance. Keyword: Organization Culture, Competency, and Compensation on the Work Performence